Skutan - A roof box for everyone - Holmer,Elin (2024)
A roof box is an essential part of a skiing trip by car, but many users find it frustrating and time consuming to use. Interviews with users showed that they find it difficult to load and unload the roof box, since it is too high up for most people. They also expressed that it is too heavy to lift the skis above their heads and that they find it problematic that they are not able to see the inside. Market research showed that current manufacturers have not addressed these issues and therefore have missed the opportunity to create a valid solution to the problems that their users experience. During the ideation phase of the design process, I attempted to find a new way of accessing the skis in a roof box by sketching, building a mockup, testing and finding out users' opinions on what I had created. The result of the project was Skutan, a roof box where the skis and ski poles are mounted in holders on a platform that is tilted and slides down to the user for easy access. The construction is based on established mechanical technologies, such as pneumatic cylinders, that use raised air pressure to tilt the platform to alleviate physical effort for the user. Skutan offers a completely new accessibility for its users, ensuring an easy and comfortable experience regardless of the user’s height.
Keywords: Industrial design; design; product design; roof box; skiing; ski; car; user-centered design; automotive design; transportation design; ergonomics; user needs; roof box design; market research; design iterations; design process; sketching; prototyping; CAD; innovation